Chiral CuS nanoparticles and their photothermal properties. Issue 27 (23rd June 2022) - Gu, Yarong; Wang, Wenhe; Gao, Chenqi; Feng, Lingyan; Wu, Jinbo; Zhao, Lijuan
Abstract : Chiral CuS NPs were prepared through a ligand-exchange process and CPL-controlled photothermal performance was realized. Abstract : Semiconductor nanoparticles (NPs) with chiroptical activity are emerging candidates for photothermal agents that respond to circularly polarized light (CPL). Herein, CuS NPs capped with citrate (cit-CuS NPs) were prepared by a solution method. The chiral enantiomers l -CuS and d -CuS NPs were obtained by ligand exchange with cysteine (Cys). New mirrored signals in the UV and visible range were observed in the circular dichroism (CD) spectra of samples, indicating that the chirality of Cys was successfully transferred to the CuS NPs. In addition, the photothermal response of chiral samples showed a preference for CPL. The maximum photothermal conversion efficiency reaches up to 59.15% for d -CuS NPs under right-circularly-polarized light (RCPL). This work realized CPL-controlled photothermal performances, providing a new strategy for chiral NP-supported photothermal therapy.